Mycetophila strobli Lastovka 1972 ... - Polevoi, A. V.; Maximova, Yu. V.; Subbotina, E. Yu. (Zenodo, 2020)
Mycetophila strobli Laštovka, 1972 MATERIAL. 1 ♂, Pyasina, 9– 13.08.2015 (UTR). DISTRIBUTION. Palaearctic, widely distributed [Zaitzev, 2003; Jurgenstern et al., 2015]. ... : Published as part of Polevoi, A. V., Maximova, Yu. V. & Subbotina, E. Yu., 2020, New data on the fungus gnats (Diptera: Bolitophilidae, Keroplatidae, Mycetophilidae) of the Taimyr Peninsula with a description of two new species of the genus Boletina Staeger, pp. 315-326 in Russian Entomological Journal 29 (3) on page 320, DOI: 10.15298/rusentj.29.3.13, http://zenodo.org/record/13165149 ...